Basic Aspects of Catechol-O-Methyltransferase and the Clinical Applications of its Inhibitors - Nissinen, Erkki (International review of neurobiology, 2010)
"Since its discovery in 1958, the Catechol-O-methyltransferase (COMT) enzyme has generated a lot of excitement, particularly so in more recent years with the discovery of clinically relevant COMT inhibitors in the late 1980's. While the volume of published research on the COMT enzyme and its inhibitors is substantial, there is no comprehensive, up-to-date source containing all the information available on basic COMT biochemistry and pharmacology, as well as critical review of results from clinical trials. This volume of International Review of Neurobiology summarizes what is currently known about COMT enzyme: its genomics, structure, function and biochemical properties; and presents up-to-date evaluation of the clinical use of COMT inhibitors as an adjunct to levodopa/dopa decarboxylase inhibitor treatment in Parkinson's disease."--Publisher's description.